2016
DOI: 10.1387/ijdb.160040mk
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic protein 4 promotes craniofacial neural crest induction from human pluripotent stem cells

Abstract: Neural crest (NC) cells are a group of cells located in the neural folds at the boundary between the neural and epidermal ectoderm. Cranial NC cells migrate to the branchial arches and give rise to the majority of the craniofacial region, whereas trunk and tail NC cells contribute to the heart, enteric ganglia of the gut, melanocytes, sympathetic ganglia, and adrenal chromaffin cells. Positional information is indispensable for the regulation of cranial or trunk and tail NC cells. However, the mechanisms under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 29 publications
(59 reference statements)
0
22
0
Order By: Relevance
“…35 However, the observed hDPC-BMP4 NCSC phenotype, as well as the improved changes observed during their neural differentiation in vitro, support the important role of BMP4 in sensory neuron and cranio-facial neural crest induction. 17,30,42,43 To provide further evidence of the importance of BMP4 for the NCSC phenotype and neural differentiation, we also tested the effect of supplementing hDPC- Notably, the characterization of dental-related human NCSCs, including those derived from gingival tissue, periodontal tissue, exfoliated deciduous teeth, and adult human dental pulp, has gained increasing interest for their potential use in neurodegenerative disorders. Nevertheless, most reports are limited to describing the molecular resemblance to neural crest cells, while their actual differentiation capacity is usually left untested, masking their actual translational potential for regenerative medicine.…”
Section: Discussionmentioning
confidence: 99%
“…35 However, the observed hDPC-BMP4 NCSC phenotype, as well as the improved changes observed during their neural differentiation in vitro, support the important role of BMP4 in sensory neuron and cranio-facial neural crest induction. 17,30,42,43 To provide further evidence of the importance of BMP4 for the NCSC phenotype and neural differentiation, we also tested the effect of supplementing hDPC- Notably, the characterization of dental-related human NCSCs, including those derived from gingival tissue, periodontal tissue, exfoliated deciduous teeth, and adult human dental pulp, has gained increasing interest for their potential use in neurodegenerative disorders. Nevertheless, most reports are limited to describing the molecular resemblance to neural crest cells, while their actual differentiation capacity is usually left untested, masking their actual translational potential for regenerative medicine.…”
Section: Discussionmentioning
confidence: 99%
“…In our recent study (Mimura et al, 2016), we demonstrated a two-step NC induction method: (1) the activation of WNT and FGF signaling on days 0-8 for early NC specification and (2) the activation of BMP signaling in combination with WNT and FGF signaling on days 8-12 ( Figure 3a). Activating BMP signaling at specific time points appears critical for the induction of cranial mesenchyme from early NC cells (Figure 3b).…”
Section: Induction Of Craniofacial Mesenchyme From Hpscsmentioning
confidence: 95%
“…Microarray analysis demonstrated the upregulation of cranial NC genes in the induced craniofacial mesenchyme (Figure c). These BMP‐treated NCCs can differentiate into osteocytes and chondrocytes (Mimura et al , ). These results indicate that BMP signaling regulates cranial positioning during NC differentiation from hPSCs.…”
Section: Induction Of Craniofacial Mesenchyme From Hpscsmentioning
confidence: 99%
See 1 more Smart Citation
“…in a 3D bioengineering microenvironment where neural crest cells are encapsulated in gelatin-based photo-cross-linkable hydrogels and cultured for about 3 weeks to efficiently drive differentiation (Namkoong et al, 2016). In addition, CNCs supplemented with BMP4 in the culture media are capable of differentiating into osteocytes and chondrocytes (Mimura et al, 2016). Mouse embryonic stem cells can be selectively differentiated into cranial NC stem cells, which can further differentiate into other cell types including osteoblasts (Minamino et al, 2015).…”
Section: Neural Crest Cells and Regenerative Medicinementioning
confidence: 99%